SYMBOL OF FEAR IN RUMAAN ALAM’S “LEAVE THE WORLD BEHIND” - Andayani, Ambar; Fajar Deanova R., Putra (La Ogi : English Language Journal, 2026)
Fear in contemporary literature is often represented not through explicit violence but through ambiguity and symbolic elements. This study examines how fear is constructed symbolically in Rumaan Alam’s Leave the World Behind. Drawing on Frederick William Dillistone’s theory of symbolism, this research interprets symbols as visible signs that represent invisible psychological realities. To strengthen the analysis, Starkstein’s concept of fear is applied to explain how uncertainty and the absence of information shape the characters’ emotional responses. This study employs a qualitative descriptive method, using narrative descriptions, dialogues, and events from the novel as primary data. The findings reveal that darkness functions as the dominant symbol of fear, representing confusion, loss of control, and psychological instability caused by the unexplained blackout. In addition, the black color symbolizes death, danger, and the unknown, particularly through images of animal corpses and abnormal animal behavior. These symbols collectively construct an atmosphere of anxiety and uncertainty, emphasizing that fear in the novel emerges from ambiguity rather than direct confrontation with visible threats. This study contributes to literary studies by demonstrating how symbolic strategies are used to represent psychological fear in contemporary fiction.